Time-based prospective memory in preschoolers – the role of time monitoring behavior - Szpakiewicz, Elżbieta; Józefacka, Natalia Maja (Frontiers in Psychology, 2024)
Background Time-based prospective memory (TBPM) refers to the ability to remember to perform an intended activity at a specific time in the future or after a specific time interval. This article reviews TBPM memory in preschool children and explores the role of time monitoring behavior in TBPM performance. Methods A total of 242 preschool-aged children (aged 2–6) performed a prospective memory task, wherein prospective memory accuracy, ongoing task performance, and time monitoring activity were assessed. Additionally, the study examined the relationship of various cognitive abilities to TBPM performance through the use of appropriate cognitive tasks. Results The first signs of TBPM were observed in children as young as 2 years old. No significant age differences were identified; preschoolers can perform a delayed intention on their own initiative at a certain point in the future only to a minimal extent. The majority of variance in TBPM performance could be explained by time checking behavior. Conclusion The current study indicated that even 2-year-olds can perform TBPM at a basic level when the task is sufficiently understandable. While many cognitive abilities are correlated with TBPM performance, it appears that only time checking behavior plays a significant role in TBPM among preschoolers.